2021
DOI: 10.1038/s41598-021-81635-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bond dynamics of interfacial water molecules revealed from two-dimensional vibrational sum-frequency generation spectroscopy

Abstract: Vibrational sum-frequency generation (vSFG) spectroscopy allows the study of the structure and dynamics of interfacial systems. In the present work, we provide a simple recipe, based on a narrowband IR pump and broadband vSFG probe technique, to computationally obtain the two-dimensional vSFG spectrum of water molecules at the air–water interface. Using this technique, to study the time-dependent spectral evolution of hydrogen-bonded and free water molecules, we demonstrate that at the interface, the vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…15. The vSFG was calculated using the surface-specific velocity-velocity correlation function approach [29][30][31], i.e. where χ abc 2 is the resonant component of susceptibility, while r OH j and ṙOH j refer to the intramolecular distance and velocity of a given OH mode, respectively.…”
Section: B Frequency Fluctuation Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…15. The vSFG was calculated using the surface-specific velocity-velocity correlation function approach [29][30][31], i.e. where χ abc 2 is the resonant component of susceptibility, while r OH j and ṙOH j refer to the intramolecular distance and velocity of a given OH mode, respectively.…”
Section: B Frequency Fluctuation Dynamicsmentioning
confidence: 99%
“…However, the interpretation of the observed vSFG spectrum is complicated, as there is no direct way for uniquely decomposing the observed peaks. In this context, several molecular dynamics (MD) studies have been performed to interpret the relationship between the vibrational spectrum and the vibrational dynamics of interfacial water molecules * tkuehne@cp2k.org [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Previous simulation studies have shown that the hydrogen-bonded network becomes less structured at the interface, with an enhanced population of single donor (SD) configurations, which is basically attributed to the sharp peak around 3700 cm −1 [8,33].…”
Section: Introductionmentioning
confidence: 99%
“…23–25 Third-order nonlinear spectroscopic techniques like two-dimensional infrared spectroscopy (2D-IR) and 3-pulse photon echo spectroscopy (3PEPS) open the avenue to study the time-dependent evolution of the vibrational Eigenstates or measure ultra-fast vibrational dephasing. 25–38 In our present work, we have applied a static electric field of strength 0.025 V Å −1 and 0.25 V Å −1 and studied the field effect on vibrational dynamics of liquid water (D 2 O) and eventually compared with the vibrational dynamics of OD modes in ambient conditions. While a weak field of 0.025 V Å −1 can be attained in an electrochemical cell, a local field of 0.25 V Å −1 can be generated near the surface by scanning tunneling microscopic (STM) probe.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 The timescale of vibrational dephasing of OD modes was obtained using spectral analysis and statistical approaches like frequency-time correlation function and time-dependent frequency probability distributions. 32–36…”
Section: Introductionmentioning
confidence: 99%
“…25,26 We have furthermore recently reported the differences in the p K w /p K a of water isotopologues including HDO and HTO. 27 NQEs in H 2 O, light water, have been extensively studied in the context of water clusters, 28,29 in ambient water, 30–33 in high temperature water, 34 and in terms of the critical point of water, 35 the water autoionization constant (p K w ), 36 protonated and deprotonated water, 37,38 water–vapor interfaces, 39,40 and water–metal interfaces. 41,42…”
Section: Introductionmentioning
confidence: 99%